Perancangan UI/UX aplikasi Kabupaten Semarang Virtual Tourism Destination menggunakan metode Goal Directed Design - Handika, Rosalina Dyah; Nugroho, Adi (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2025)
Semarang Regency is a tourism destination rich in natural beauty, cultural diversity, and fascinating historical heritage. Innovation is needed to optimize the potential of tourism by providing information to tourists. This research applies the Goal Directed Design (GDD) method to design the Semarang Regency Virtual Tourism Destination application called